2011
DOI: 10.1039/c1an15675f
|View full text |Cite
|
Sign up to set email alerts
|

A disposable sensor for point of care wound pH monitoring

Abstract: The development of a disposable pH sensor for the point of care monitoring of wound pH is described. The system exploits the pH dependence of an endogenous biomarker (urate) to yield an unambiguous signal. The sensor responses have been characterised and the responses validated in whole blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 12 publications
2
44
0
Order By: Relevance
“…5 Thus far, different methods have been reported for measuring the pH, including colorimetric methods, 6 electromechanical 7 and electrochemicalbased techniques. 8 All of these methods are useful but they have some disadvantages, such as sophisticated technologies, high cost production and difficult usage. Hence, an economic, simple and applicable method for monitoring pH during the wound healing process should be developed.…”
Section: Introductionmentioning
confidence: 99%
“…5 Thus far, different methods have been reported for measuring the pH, including colorimetric methods, 6 electromechanical 7 and electrochemicalbased techniques. 8 All of these methods are useful but they have some disadvantages, such as sophisticated technologies, high cost production and difficult usage. Hence, an economic, simple and applicable method for monitoring pH during the wound healing process should be developed.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the carbon particles within the ink formula consisting of predominantly basal planes. 24,25 The response to ferrocyanide after the electro-deposition of the gold stands in marked contrast with superior peak definition. The peak magnitude of the gold SPE is more than double that of the bare carbon with increased reversibility of the redox system where the peak separation has decreased to 71 mV.…”
Section: ¹1mentioning
confidence: 99%
“…24,25 This process was also instituted here where it has been found that the unmodified screen-printed electrodes typically exhibit poor electrochemical behavior with large overpotentials necessary to obtain any significant analytical responses. 24 The electrodes were further modified through the electrodeposition of a gold layer. This was achieved through employing cyclic voltammetry whereby the pre-anodized screen-printed electrode was immersed in a gold(III) chloride solution (6 mM NaAuCl 4 , 0.1 M HNO 3 ) and scanned between ¹0.2 and 1.6 V for 20 scans at 0.1 V s…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of pH to a range of biochemical processes, including the activity of proteolytic enzymes, the ability to monitor pH and modulate it (through treatments and dressings) could be advantageous. New technologies are emerging to enable monitoring of pH in wounds, based upon electrochemical methods using potentiometric and voltammetric methodologies [9][10][11], inductance-based pH responsive hydrogels [12], optical fiber based sensors [13], and luminescence approaches through sensor films [14]. Investigators have also tried to elucidate whether there is a spatial disparity to pH.…”
Section: Ph: a Key Biomarker?mentioning
confidence: 99%